Management of pulp canal obliteration using the Modified-Tip instrument technique - Siddiqui, Shoaib Haider (International Journal of Health Sciences, 2015)
The incidence of pulp canal obliteration following dental trauma has been reported to be approximately 4 - 24% and its management can be quite challenging for the practitioner. Locating the canal and negotiating it to full working length may lead to iatrogenic errors such as fractured instrument and perforation. This case report deals with such a case using the modified tip instrument technique to gain access and negotiate the canal to the apex followed by conventional root canal preparation and obturation. Keywords: Pulp canal obliteration, Calcific metamorphosis, Management, Root Canal.